Corticosterone Levels and Glucocorticoid Receptor Gene Expression in High Drinking in the Dark Mice and Their Heterogeneous Stock (HS/NPT) Founder Line - Savarese, Antonia M.; Grigsby, Kolter B.; Jensen, Bryan E.; Borrego, Marissa B.; Finn, Deborah A.; Crabbe, John C.; Ozburn, Angela R. (Frontiers in Behavioral Neuroscience, 2022)
The High Drinking in the Dark (HDID-1) line of mice has been selectively bred for achieving high blood alcohol levels (BALs) in the Drinking in the Dark task, a model of binge-like drinking. Recently, we determined that glucocorticoid receptor (GR) antagonism with either mifepristone or CORT113176 (a selective GR antagonist) reduced binge-like ethanol intake in the HDID-1 mice, but not in their founder line, HS/NPT. Here, we examined whether the selection process may have altered glucocorticoid functioning by measuring (1) plasma corticosterone levels and (2) expression of the genes encoding GR (Nr3c1) and two of its chaperone proteins FKBP51 and FKBP52 (Fkbp5 and Fkbp4) in the brains (nucleus accumbens, NAc) of HDID-1 and HS/NPT mice. We observed no genotype differences in baseline circulating corticosterone levels. However, HDID-1 mice exhibited a greater stimulated peak corticosterone response to an IP injection (of either ethanol or saline) relative to their founder line. We further observed reduced basal expression of Fkbp4 and Nr3c1 in the NAc of HDID-1 mice relative to HS/NPT mice. Finally, HDID-1 mice exhibited reduced Fkbp5 expression in the NAc relative to HS/NPT mice following an injection of 2 g/kg ethanol. Together, these data suggest that selective breeding for high BALs may have altered stress signaling in the HDID-1 mice, which may contribute to the observed selective efficacy of GR antagonism in reducing binge-like ethanol intake in HDID-1, but not HS/NPT mice. These data have important implications for the role that stress signaling plays in the genetic risk for binge drinking.